Unbundling Institutions - Acemoglu, Daron; Johnson, Simon (Journal of Political Economy, 2005)
This paper evaluates the importance of "property rights institutions," which protect citizens against expropriation by the government and powerful elites, and "contracting institutions," which enable private contracts between citizens. We exploit exogenous variation in both types of institutions driven by colonial history and document strong first‐stage relationships between property rights institutions and the determinants of European colonization strategy (settler mortality and population density before colonization) and between contracting institutions and the identity of the colonizing power. Using this instrumental variables approach, we find that property rights institutions have a first‐order effect on long‐run economic growth, investment, and financial development. Contracting institutions appear to matter only for the form of financial intermediation. A possible explanation for this pattern is that individuals often find ways of altering the terms of their formal and informal contracts to avoid the adverse effects of weak contracting institutions but find it harder to mitigate the risk of expropriation in this way.